A Review of Drug-Induced Hepatotoxicity and Diclofenac Induced Biochemical Changes in Hepatotoxicity: Understanding the Mechanisms and Implications (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study was conducted to demonstrate drug-induced hepatotoxicity and Diclofenac-inducedhepatotoxicity.The chemical substances which cause liver injury are called hepatotoxins orhepatotoxicants. Hepatotoxicants are exogenous compounds of clinical relevance and may includeoverdoses of certain medicinal drugs, industrial chemicals, natural chemicals (microcystins), herbalremedies and dietary supplements. The drug-induced hepatotoxicity, at all phases of drug developmentthat includes the pre-clinical toxicity studies, the different phases of clinical trial including the postmarketingsurveillance.The Drug Induced Liver Injury (DILI) is defined as the injury caused by exposureto a drug or non-infectious toxic agent and is associated with different levels of organ dysfunction.